Social representations of Libras as a mandatory subject by actors from schools in public and private schools in the Municipality of Guarabira-PB (Research, Society and Development, 2021)
The present study aimed to apprehend the social representations of students and teachers of basic education in the Municipality of Guarabira / PB with regard to the inclusion of the discipline Libras in schools. As a theoretical contribution, the theory of social representations was chosen, as it allows understanding how social subjects conceive everyday events - information, feelings and social experiences - related to the area of ​​deafness. As a methodological support, a field research was carried out, with a qualitative and quantitative approach, composed of a non-probabilistic and convenience sample, formed by 50 subjects, 22 students of the pedagogy course and 18 teachers of basic education held in public and private schools. For data collection, a socio-demographic questionnaire and the Associação Livre de Palavras technique were used, whose inducing stimuli were: deaf; pounds; social inclusion of the deaf; inclusion of the discipline of pounds in the school. The data from the free association were processed and analyzed by the Tri-Deux-Mots software, through the correspondence factor analysis. The “Libras” stimulus was represented as: “something produced by the hands”, a “sign language”, which provides “teaching and help”, being, therefore, a “sign language”. The results pointed out the relevance of the study of social representations in terms of their importance and obligation in learning Libras. It provided a better understanding in the urgency of debates and discussions about the valorization and popularization for society, as well as in the didactic-pedagogical training and expansion as a teaching and learning tool in the researched universe.